Meeting report: CEPI workshop on Rift Valley fever epidemiology and modeling to inform human vaccine development, Nairobi, 4–5 June 2024 - Gharpure, R.; Vegvari, C.; Abdissa, A.; Alimi, Y.; Anyamba, A.; Auerbach, J.; Bett, Bernard K.; Bird, B.H.; Bob, N.S.; Breugelmans, J.G.; Clark, J.; Cleaveland, S.; et al. (Elsevier, 2025)
Rift Valley fever (RVF) is a zoonotic viral disease that causes epidemics and epizootics among humans and livestock, resulting in substantial health and socioeconomic consequences. Currently, there are no RVF vaccines licensed for humans, but several candidates show promise in early-stage development. Existing gaps in RVF epidemiological data and challenges associated with predicting RVF outbreak risk complicate the planning of efficacy studies, making the pathway to licensure for promising candidates unclear. In June 2024, the Coalition for Epidemic Preparedness Innovations (CEPI) convened a two-day workshop in Nairobi, Kenya, to discuss RVF epidemiology, modeling priorities, and specific gaps relevant to human RVF vaccine development. The workshop included representatives from multiple RVF-endemic countries, key global collaborators, and international health organizations.